1995
DOI: 10.1021/bi00041a017
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, and cloning of a heme-binding protein (23 kDa) in rat liver cytosol

Abstract: A heme-binding protein (designated HBP23) has been purified from rat liver cytosol using heme-affinity chromatography and either reverse-phase high-performance liquid chromatography or sequential ion-exchange chromatography. The protein (23 kDa) binds heme with an affinity (Kd = 55 nM) higher than that of the abundant cytosolic heme-binding proteins, heme-binding protein (HBP)/liver fatty acid-binding protein (L-FABP) and the glutathione S-transferases (GSTs) (Kd = 100-200 nM). HBP23 is present in the cytosol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
94
1
5

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 34 publications
5
94
1
5
Order By: Relevance
“…The same report also documented that overexpression of Prx-II protected cells from gamma irradiation. Cytoprotection by Prx-II in response to numerous stimuli has been well documented by others (Iwahara et al, 1995;Netto et al, 1996;Berggren et al, 2001) and by us . In contrast to the results of Park et al, our results showed that Prx-I, instead of Prx-II, expression was induced by ionizing radiation in human HT29 and rat C6 glioma cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The same report also documented that overexpression of Prx-II protected cells from gamma irradiation. Cytoprotection by Prx-II in response to numerous stimuli has been well documented by others (Iwahara et al, 1995;Netto et al, 1996;Berggren et al, 2001) and by us . In contrast to the results of Park et al, our results showed that Prx-I, instead of Prx-II, expression was induced by ionizing radiation in human HT29 and rat C6 glioma cells.…”
Section: Discussionmentioning
confidence: 54%
“…Structure details of several Prx family members have been worked out through X-ray crystallography (Choi et al, 1998;Hirotsu et al, 1999;Schroder et al, 2000). The fact that amino acid sequences and antioxidative functions of Prxs are highly conserved through evolution signifies the importance of these enzymes in cell survival (Shau and Kim, 1994;Iwahara et al, 1995;Prospaeri et al, 1998). Park et al recently showed that levels of human Prx-II were associated with resistance of cells to radiation therapy and that Prx-II antisense served as a radiosensitizer (Park et al, 2000).…”
mentioning
confidence: 99%
“…Peroxiredoxins are in different subcellular compartments. While Prx III is localized to mitochondria [12,22,54,55], Prx I and Prx II are found in the cytoplasm [15,23,32,43]. Furthermore Prx I is thought to be translocated into the nucleus by association with other proteins such as tyrosine kinase c-Abl, though given its small size it could enter passively [34].…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected by the numerous synonyms used. Thus Prx I is further known as MSP23 (mouse macrophage stress protein M r 23 K) [30], OSF3 (mouse osteoblast specific factor 3) [31], HBP23 (heme-binding protein M r 23 K) [32], PAG (proliferation-associated gene) [10] and NKEF-A (human natural killer cell-enhancing factor-A) [33]. Prx I is a physiological inhibitor of cAbl kinase activity [34].…”
mentioning
confidence: 99%
“…Interestingly, a 23 kDa heme-binding protein, termed HBP23, is shown to be expressed in the cytosol of the liver, kidney, spleen, small intestine and heart cells [148,149]. Another 21 kDa heme-binding protein, termed p22 HBP, is shown to be induced by heme in mouse erythroleukemia cells [148,150]. These proteins may play important roles in heme metabolism in diverse cells.…”
Section: The Oxidant Potential Of Heme Is Neutralized By Multiple Hemmentioning
confidence: 99%